Collaboration of public agencies in innovation and startups in Malaysia - Beh, L.S. (2018)
•The implementation of creativity and innovation in public administration is crucial to driving Malaysia towards becoming a developed country. •Indeed, many governments have embarked on the innovation aspects of the agenda of policymakers. •The adoption of innovations in the public administration sector is seen as a complex process. •Innovation implementation in public administration depends on the individual’s motivation to innovate as well as their readiness to adapt innovation implementation to the environment.